Nonequilibrium action principles for quasi-ﬁeld - Burgess, M. (Condensed Matter Physics, 2000)
Quasiparticle descriptions of nonequilibrium physics hold the promise of
tracking the relevant degrees of freedom in calculations of statistical systems, as well as providing an important formal perspective on quantum
ﬁeld theories away from equilibrium. A formulation of nonequilibrium, quasiparticle ﬁeld theory is presented here. The Schwinger closed time path
generating functional and generalized sources are used to develop schematic ﬁeld theories which can be adapted to real problems. The importance
of the source method for effective nonequilibrium theories is argued and the
physical interpretation of the formalism is discussed, including its possible
applicability to biological dynamics. Квазічастинкові описи нерівноважної фізики дозволяють простежувати відповідні ступені вільности в обчисленнях статистичних систем
і забезпечують важливий формальний підхід до квантової теорії поля
поза рівновагою. Тут запропоновано формулювання нерівноважної
квазічастинкової теорії поля. Для розвитку схематичних теорій поля,
здатних описувати реальні системи, використовуються швінґерівський твірний функціонал за шляхами, замкненими в часі, і узагальнені
джерела. Обґрунтовується важливість методу джерел для ефективних нерівноважних теорій, а також його застосовність до біологічної
динаміки.